Effect of the COVID-19 pandemic on access to primary percutaneous coronary intervention for ST-segment elevation myocardial infarction - Göksel Çinier; Mert Hayıroğlu; Levent Pay; Ahmet Yumurtaş; Ozan Tezen; Kemal Emrecan Parsova; Ilker Tekkesin (KARE Publishing, 2020)
Objective: The coronavirus disease 2019 (COVID-19) pandemic caused by the emergence of severe acute respiratory syndrome coronavirus 2 has resulted in a health crisis and a significant number of deaths worldwide. The full effect on access to medical care and the treatment for patients with chronic diseases and acute conditions is still unknown. This is an investigation of access to primary percutaneous coronary intervention (PPCI) for patients diagnosed with ST-segment myocardial infarction (STEMI) during the pandemic. Methods: Consecutive patients who were diagnosed with STEMI and underwent PPCI during the ongoing COVID-19 pandemic were included in the study. Clinical and angiographic characteristics of the patients were assessed. A control group of patients diagnosed with STEMI and who underwent PPCI during the same time interval a year prior to the outbreak of the disease was analyzed retrospectively for comparison. Results: There was a significant reduction in the number of STEMI cases during the COVID-19 crisis period. Furthermore, these patients had a prolonged ischemic time; they were more likely to have a longer pain-to-balloon (Odds ratio [OR]: 2.0, 95% confidence interval [CI]: 1.1-10.2) and door-to-balloon time (OR: 5.4, 95% CI: 3.1-22.8). Conclusion: Patients diagnosed with STEMI during the pandemic experienced a significant delay between the onset of symptoms and PPCI.